Wykorzystanie STEAM-owego projektu w kształtowaniu wybranych pojęć geometrycznych u przedszkolaków - Agnieszka Bojarska-Sokołowska (Problemy Wczesnej Edukacji)
The article presents the concept of using steam design in the shaping of geometric concepts in preschool children. Attention was paid to shaping the spatial imagination of children, i. e. developing spatial orientation, discovering the properties of solids and the concept of symmetry. However, mathematical knowledge was not treated as a separate field of knowledge, but as a tool to solve a specific problem, which in this study is the creation of a tourist, mobile guide.